2018
DOI: 10.7186/bgsm65201806
|View full text |Cite
|
Sign up to set email alerts
|

Lower Miocene planktic foraminifera from the Temburong Formation in Menumbok, Klias Peninsula, Sabah

Abstract: Lower Miocene sedimentary rocks of the Temburong Formation exposed at Kg. Assam, Menumbok, Klias Peninsula were examined for planktic foraminifera analysis. Four shale samples were collected and processes were done based on the standard micropaleontological method. This assemblage allows two local biozones to be recognized, namely the Globigerinoides primordius Zone (N4 zone) and the second assemblage belongs to the Globoquadrina dehiscens-Globoquadrina praedehiscens Zone (N5 zone). This study also indicates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The identification of the Ophiomorpha rudis subichnofacies within the formation samples suggested occupying the submarine fan system (Jasin and Firdaus, 2019). Supported by the identification of the lower Miocene (N4 and N5 Blow Zone) planktic foraminifera which is equivalent to its paleoenvironment (Asis, Tahir, Musta, et al, 2018b) The paleoecological system eventually originated from the photic zone environment which is the top layer that nearest to the surface of the ocean. Most of this environment is exposed to sunlight and enough light penetrates allowing for the photosynthesis process.…”
Section: Paleoenvironmental Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…The identification of the Ophiomorpha rudis subichnofacies within the formation samples suggested occupying the submarine fan system (Jasin and Firdaus, 2019). Supported by the identification of the lower Miocene (N4 and N5 Blow Zone) planktic foraminifera which is equivalent to its paleoenvironment (Asis, Tahir, Musta, et al, 2018b) The paleoecological system eventually originated from the photic zone environment which is the top layer that nearest to the surface of the ocean. Most of this environment is exposed to sunlight and enough light penetrates allowing for the photosynthesis process.…”
Section: Paleoenvironmental Analysismentioning
confidence: 92%
“…The research was conducted at Klias Peninsula which is underlain by Paleogene-Neogene sediment, Crocker Formation, Temburong Formation, Setap Formation and Liang Formation. A previous study had suggested that the shale unit of Temburong Formation was deposited as a distal part of a deep-sea fan deposited based on the planktonic foraminifera analysis (Asis et al, 2018a). The age of the Temburong Formation is considered at late upper Oligocene to lower Miocene (N4 to N5 zones).…”
Section: Introductionmentioning
confidence: 99%
“…Madon (1997) reported the argillaceous Temburong Formation having thin sandstone units interbedded with shale and siltstones in Labuan, Sabah. The Temburong Formation in Tenom area and Klias Peninsula, SW Sabah is principally containing fine-grained turbidites (Td and Te Bouma Sequence), which are representative of basin plain facies and was interpreted as the distal part of a deep marine fan (Asis et al, 2015;2018). Abdullah et al (2017) described the Temburong Formation as deep marine shale and sandstone units located in Sipitang-Tenom area of West Sabah.…”
Section: Sedimentary Faciesmentioning
confidence: 99%